THE The Correlation Between Reading Habit and Students’ Reading Comprehension In English I Subject at Economic College of Riau - Bishry, Hasanul (Komunitas Manajemen Kompetitif, 2021)
This research was motivated by students’ comprehension in reading. In teaching and learning process, students should be able to understand the text, analyze the text and interpret the text. Students could improve their achievement when they understand the text. In some cases, students were difficult to understand the text, they also could not be able to find the meaning of the text and author’s idea. Based on this case, the purpose in this research was to investigate the correlation between students’ reading habit on their reading comprehension. This research used quantitative method. The design in this research was a correlational research. The subject in this research was the students in fifth semester at STIE Riau. The sample used cluster sampling. The data collection used questionnaire and test. Then, the data was analyzed by SPSS Computation with correlational design. The finding in this research showed that there was correlation between reading habit and reading comprehension. The correlation between variable was in strong correlation.